A three-dimensional etch method for nitrides and carbonitrides in steel
Patent Information
- Application Number
- CN202611235375.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-23
AI Technical Summary
⑴ 相较于现有恒流模式电解方法,本发明采用恒电压模式有效克服微合金钢和合金钢绝缘物相(弱导电物相)引发的钝化问题,保障腐刻过程持续完整推进;本发明采用恒电压模式,锁定电极电位,使电流随界面状态自适应调节:当绝缘相在界面积聚、界面阻抗升高时,电流产生漂移并出现突跃,击穿绝缘相累积形成的钝化膜,保障电解腐刻持续推进,恒电压模式下电极电位保持恒定,腐刻速率平稳、试样表面平整度更均匀。
Smart Images

Figure CN122961766A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal material analysis and characterization, and specifically to a three-dimensional etching electrolysis method for nitrides and carbonitrides in steel. Background Technology
[0002] Microalloy steel refers to low-alloy steel with trace amounts of strong carbonitride-forming elements such as Nb, V, Ti, and Al added (the total amount of alloying elements usually does not exceed 0.20%). This results in high strength and toughness through precipitation strengthening of nitrides and carbonitrides, as well as grain refinement mechanisms. Alloy steel refers to steel containing a higher proportion of alloying elements such as Cr, Ni, Mo, V, and W (the total amount is usually not less than 5%), possessing special mechanical or physicochemical properties. It is widely used in gears, bearings, molds, heat-resistant and corrosion-resistant structural components, and other fields. Both types of steel intentionally incorporate higher levels of alloying elements: on the one hand, elements such as Nb, V, Ti, and Al precipitate in the steel to form nitrides such as VN, TiN, and AlN, as well as carbonitrides such as Nb(C,N), V(C,N), and Ti(C,N); on the other hand, alloying elements such as Cr, Ni, Mo, and W significantly improve the corrosion resistance of the steel matrix, a characteristic that has a significant impact on the electrochemical corrosion process.
[0003] The precipitation behavior of nitrides and carbonitrides has a profound impact on the comprehensive properties of microalloyed steels and alloy steels. Fine, dispersed nitride / carbonitride precipitates can effectively pin austenite grain boundaries, refine grains, and provide precipitation strengthening; while coarse, aggregated, or unevenly distributed precipitates may become sites for fatigue crack initiation, deteriorating the toughness and plasticity of the steel. The three-dimensional morphology (shape, size, and aggregation state) of nitrides and carbonitrides, along with their in-situ spatial distribution in the matrix, are key parameters for quantitatively analyzing precipitation mechanisms, optimizing composition design, improving smelting-casting-rolling-heat treatment processes, and evaluating service performance, possessing significant scientific and engineering value.
[0004] Currently, the three-dimensional characterization methods for nitrides and carbonitrides in steel mainly fall into the following three categories: The acid dissolution method utilizes aqueous solutions of inorganic acids such as nitric acid, sulfuric acid, and hydrochloric acid to locally corrode the metal matrix, leaving acid-resistant precipitates on the sample surface for observation. However, nitrides and carbonitrides are not completely inert to strong acids; acidic solutions can cause varying degrees of chemical corrosion, leading to distorted morphology of the precipitates and making it difficult to accurately reflect their original three-dimensional characteristics.
[0005] Extraction analysis (large-sample electrolysis) completely decomposes the steel matrix through electrochemical dissolution, causing precipitated phase particles to detach from the matrix and enter the solution. The particles are then collected through filtration, washing, and drying, and analyzed using scanning electron microscopy and X-ray diffraction (patents CN118408796A, CN202158981U, CN107541728B, CN110618003A, CN119394754B, etc., all belong to this technical route). This method is cumbersome, and because the precipitated phase particles are completely detached from the matrix, it is impossible to obtain information on the in-situ spatial distribution of the precipitated phase in the steel and its interaction with the surrounding microstructure.
[0006] In-situ electrolytic etching utilizes the difference in electrochemical corrosion resistance between the metal matrix and the second phase. By applying a directional current, the matrix is selectively dissolved, exposing the second phase in situ on the sample surface. This allows for direct observation of its three-dimensional morphology and in-situ distribution without any separation or extraction operations. Compared to the previous two methods, in-situ electrolytic etching offers significant advantages, including ease of operation, complete preservation of in-situ information, and accurate morphology of the precipitated phase. In previous work, the inventors developed a three-dimensional in-situ etching device and method for inclusions in steel based on a constant current electrolysis mode (ZL202010397749.X). Based on this, a series of in-situ three-dimensional etching studies were conducted on carbides and non-metallic inclusions in various steel grades, verifying the feasibility of this technical approach. All of the above studies employed a constant current (constant current density) electrolysis mode, achieving controllable dissolution of the matrix by controlling a fixed current density.
[0007] The inventor's previous applications, "An in-situ three-dimensional electrolytic etching solution and electrolytic etching method for second-phase particles in stainless steel (ZL202011600956.7)," "A three-dimensional etching method for carbides in GCr15 bearing steel (ZL202011604199.0)," "A three-dimensional etching characterization method for non-metallic inclusions in high-nickel martensitic aging steel (ZL202011604047.0)," and "A three-dimensional etching method for inclusions in chromium-manganese stainless steel (ZL202011610884.X)," all employ a three-dimensional etching device for inclusions and a constant current electrolytic etching method.
[0008] However, when the above-mentioned constant current electrolytic etching technology is applied to the three-dimensional characterization of nitrides and carbonitrides in microalloyed steel and alloy steel, there are two technical obstacles that are difficult to overcome.
[0009] First, microalloyed steel and alloy steel share common alloying characteristics. Alloying elements such as Cr, Ni, Mo, Nb, V, and Ti significantly improve the corrosion resistance of the matrix, and the electrochemical dissolution rate of the steel matrix is significantly lower than that of ordinary carbon steel. In addition, the conductivity of nitrides (VN, TiN, AlN, etc.) and carbonitrides (Nb(C,N), V(C,N), Ti(C,N), etc.) is much weaker than that of the metal matrix. During the electrolytic etching process, near the pits where the matrix preferentially dissolves, insulating etching products such as oxides will gradually accumulate, as well as a large number of oxide, nitride / carbonitride particles with weak conductivity suspended at the electrolytic front. These phases accumulate at the electrolytic interface, forming a locally high-resistivity barrier layer, which leads to passivation during the electrolytic process.
[0010] In constant current (constant current density) electrolysis mode, the control system is forced to maintain a constant current output. Once the aforementioned barrier layer forms, the system's equivalent resistance rises sharply. The control system automatically increases the voltage across its terminals to maintain a constant current. However, this compensation mechanism cannot overcome the insulating barrier layer itself—the electrolytic reaction in the locally high-resistance region has been substantially interrupted, and simply maintaining the current cannot allow the passivated area to recover automatically. Simultaneously, the increased voltage exacerbates over-corrosion in other exposed areas, resulting in uneven etching. Exposed nitrides / carbonitrides are at risk of detachment. Once this passivation phenomenon occurs, it is often difficult to self-heal in constant current mode, ultimately leading to premature interruption of the electrolysis process. Nitrides and carbonitrides cannot be fully exposed, resulting in severe deterioration or even complete failure of the three-dimensional etching effect.
[0011] Secondly, the electrolyte formulation has the problem of excessive early corrosion ability, which leads to severe pitting corrosion, the formation of a large number of large-sized corrosion pits on the surface, intensified self-corrosion of the substrate, rapid consumption of electrolyte and complexing agent, poor sample flatness, and unstable electrolysis process.
[0012] In summary, existing constant current electrolytic etching technology is fundamentally inadequate for the three-dimensional in-situ characterization of nitrides and carbonitrides in microalloyed steel and alloy steel. There is an urgent need to develop a new electrolytic etching method that can overcome the aforementioned passivation phenomenon and ensure the continuous and stable operation of the electrolytic process. Summary of the Invention
[0013] The purpose of this invention is to provide a three-dimensional etching method for nitrides and carbonitrides in steel. It adopts the three-dimensional etching device for inclusions in steel used in ZL202010397749.X. By improving the power supply and electrolysis process and optimizing the electrolyte formula, the passivation phenomenon of the prior art is overcome. The electrolysis process is stable and controllable, and the three-dimensional morphology and spatial distribution of nitrides / carbonitrides in microalloyed steel and alloy steel can be obtained in detail. The operation process is simple and efficient.
[0014] The objective of this invention can be achieved through the following technical solution: a method for electrolytic etching characterization of the three-dimensional in-situ morphology of nitrides / carbonitrides in microalloyed steel and alloy steel. First, a constant voltage control power supply is introduced, and a constant voltage (constant potential) mode is used instead of a constant current mode for electrolytic etching. By locking the electrode potential and allowing the current to adaptively respond to the dynamic changes in interface impedance, the current surge actively breaks down the passivation film formed by the accumulation of the insulating phase, thereby ensuring the continuous and complete advancement of the etching process. Second, 1%~8% glycerol is added to the electrolyte formulation. As a corrosion inhibitor, it can suppress side reactions such as self-corrosion and pitting of the base metal, slow down the reaction rate, achieve a stable electrolysis effect, control the speed of the interface reaction, and avoid excessively fast early electrolytic reactions and rapid decay of later electrolytic reactions. The improved three-dimensional etching electrolytic method based on these two key features includes the following implementation steps: Step (1) Sample preparation Take the microalloy steel or alloy steel, and mechanically grind the surface to be tested sequentially with 240-mesh, 400-mesh, 600-mesh, 800-mesh, 1000-mesh, 1500-mesh, and 2000-mesh silicon carbide sandpaper. Then, mechanically polish it to a mirror finish (surface roughness Ra≤0.05 μm) with diamond polishing paste with a particle size not greater than 0.5 μm. After ultrasonic cleaning with anhydrous ethanol for 5-10 min, air dry or blow dry it in a clean and dry environment to obtain the sample to be tested. Except for the surface to be observed, the other surfaces of the sample to be tested are sealed with insulating sealing material (such as insulating glue or wax) to prevent non-observation surfaces from participating in electrolytic etching.
[0015] Step (2) Electrolyte preparation A non-aqueous organic electrolytic etching solution was prepared, which used an organic solvent as the base liquid and contained electrolytes and metal ion complexing agents. The etching solution also contained glycerol at a volume percentage of 1-8% as a corrosion inhibitor.
[0016] Step (3) Constant voltage electrolytic etching The sample to be tested is placed in the electrolytic cell of the electrolytic device; the surface of the electrolyte is used to cover the observation surface of the sample; the sample to be tested is used as the anode, and a stainless steel sheet or platinum sheet with an area not less than the exposed area of the sample to be tested is used as the cathode, with the distance between the two electrodes controlled at 20-30 mm; a constant voltage of 10V-30V is applied to the sample to be tested in constant voltage mode for electrolytic etching, the temperature is -5℃ to 5℃, and the etching time is 10 min to 60 min; During electrolytic etching, the constant electrode potential causes the current to adaptively adjust according to the interface impedance state, and the entire etching process exhibits the following typical dynamic characteristics: Initial stage of etching: The current is relatively stable, and electrolysis proceeds smoothly; Insulating phase enrichment stage: As nitrides / carbonitrides accumulate at the interface, the interfacial impedance increases and the current drift decreases slowly. At this time, the weight loss data of the electrolysis process decreases significantly, and a large amount of oxides, carbides, nitrides, and carbonitrides accumulate at the electrolysis front. Passivation film breakdown stage: When the impedance rises to the threshold, the current jumps abruptly (increases significantly within a few seconds), breaking down the local passivation film formed by the accumulation of insulating phase. Continued progress phase: Electrolysis continues to advance at the new matrix interface, and the above-mentioned "accumulation-drift-jump-progress" cycle repeats itself, accompanying the entire process of nitride / carbonitride three-dimensional etching in alloy steel and microalloy steel. The occurrence cycle and frequency are closely related to the alloy content and electrolysis parameters until the etching is completed.
[0017] Step (4) Cleaning and drying After etching, remove the sample from the electrolysis device and immediately rinse it with anhydrous ethanol to remove residual electrolyte. Then, ultrasonically clean it for 2–5 minutes and blow it dry with an inert gas (nitrogen or dry air) to prevent the sample from being exposed to air for a long time and causing surface oxidation.
[0018] Step (5) SEM morphology observation and analysis After cleaning and drying, the sample is placed directly in a scanning electron microscope (SEM) to observe the three-dimensional in-situ morphology of the exposed nitrides / carbonitrides on the etched surface using secondary electron (SE) or backscattered electron (BSE) modes. The chemical composition of the precipitated phase is analyzed by energy dispersive spectroscopy (EDS) using surface scanning or point scanning to confirm the type of precipitated phase. Further analysis of the crystal structure of the precipitated phase using electron backscattered diffraction (EBSD) can be performed to achieve a comprehensive characterization of the nitrides / carbonitrides.
[0019] The solvents mentioned in step (2) include methanol, anhydrous ethanol, etc.; the electrolytes include tetramethylammonium chloride, lithium chloride, etc.; and the metal ion complexing agents include acetylacetone, triethanolamine, γ-butyrolactone, citric acid, etc. The etching solution is one of the following four formulations (volume fraction is based on total volume, and mass concentration is expressed in g / 100ml): Formula 1: Using methanol as solvent, containing 3–10 g / 100 ml tetramethylammonium chloride, 15%–20% (volume fraction) acetylacetone, and 1%–8% (volume fraction) glycerol. This formula is suitable for microalloyed steels with V and Ti precipitation as the main components, such as MnVS-based non-quenched and tempered steel and CrMo-based quenched and tempered steel. Further optimized formulation: 5% (m / V) tetramethylammonium chloride + 15% (V / V) acetylacetone + 5% (V / V) glycerol + balance methanol.
[0020] Formula 2: Using methanol as a solvent, containing 1%–5% (volume fraction) triethanolamine, 4–10 g / 100 ml tetramethylammonium chloride, and 1%–8% (volume fraction) glycerol; suitable for microalloyed gear steels containing Cr-Mn-Ti series. Further preferred formulation: 3% (V / V) triethanolamine + 8% (m / V) tetramethylammonium chloride + 3% (V / V) glycerol + balance methanol.
[0021] Formula 3: Using anhydrous ethanol as solvent, containing 5-10 g / 100ml LiCl, 10%-15% (volume fraction) γ-butyrolactone, and 1%-8% (volume fraction) glycerol; suitable for Cr-Ni stainless steel and high alloy steel; further preferred formulation: 7% (m / V) lithium chloride + 10% (V / V) γ-butyrolactone + 8% (V / V) glycerol + balance anhydrous ethanol.
[0022] Formula 4: Using anhydrous ethanol as solvent, containing 1–10 g / 100 ml LiCl, 1–10 g / 100 ml citric acid, and 1%–8% (volume fraction) glycerol, suitable for Nb-V-Ti-N composite microalloyed steel. Further preferred formulation: 5% (m / V) lithium chloride + 8% (m / V) citric acid + 4% (V / V) glycerol + balance anhydrous ethanol.
[0023] The technical functions of each component are as follows: Tetramethylammonium chloride and LiCl act as supporting electrolytes (conductive agents) to provide ionic conductivity; acetylacetone and triethanolamine act as complexing agents to form stable complexes with the metal cations generated during dissolution, inhibiting their redeposition on the sample surface and keeping the etching interface clean; γ-butyrolactone controls the etching rate by adjusting the solution polarity; glycerol increases the solution viscosity, reduces the probability of local over-etching, controls the reaction rate, reduces the rate of pitting corrosion, and improves etching uniformity; methanol and ethanol, as non-aqueous solvents, have extremely low corrosiveness to nitrides / carbonitrides and can truly preserve the original three-dimensional morphology of the precipitated phase.
[0024] Further: In step (3), the constant voltage applied is preferably 10V to 25V; within this range, the electrolytic etching rate is moderate, the current drift and jump characteristics are significant, the etching uniformity is the best, and the exposure integrity of the precipitated phase is the highest.
[0025] Furthermore, the electrolysis temperature applied in step (3) is preferably -5℃ to 0℃. Within this range, the electrolytic etching rate is moderate, the electrolytic reaction is stable and controllable, the etching uniformity is optimal, and the electrolysis effect is good.
[0026] Further: The preferred electrolytic etching time in step (3) is 15 to 25 minutes. When the etching time is less than 15 minutes, the precipitated phase is not fully exposed from the matrix; when the etching time exceeds 25 minutes, based on the principle of similarity, the effect of extending the electrolysis time on the electrolysis effect is not significant.
[0027] Furthermore, the three-dimensional etching electrolysis rate (i.e., the rate of weight loss) is 0.001~0.2 g / min, preferably 0.002~0.08 g / min.
[0028] Furthermore, the microalloyed steel includes Mn-V series non-quenched and tempered steel, CrMo series quenched and tempered steel, Cr-Mn-Ti series gear steel, etc. Among these steel types, the precipitated phase types cover TiN, VN / V(C,N), NbN / Nb(C,N), AlN, etc., as well as their composite precipitated phases. Using the method of this invention, by selecting the corresponding electrolyte formulation and appropriately adjusting the working voltage, the three-dimensional in-situ corrosion characterization of the above-mentioned precipitated phases can be achieved.
[0029] The advantages of this invention compared to existing constant-current electrolytic etching methods are as follows: Existing technologies employ a constant-current mode where the power supply control objective is to maintain a constant current density through the sample, and the electrode potential is a passive response to changes in interfacial impedance. When the interfacial impedance increases due to the accumulation of insulating phase, the electrode potential passively increases until it exceeds the passivation range to maintain a constant current, leading to passivation failure. In contrast, this invention employs a constant-voltage mode, controlling the electrode potential difference to be constant, and the current is an active adaptive response to changes in interfacial impedance. When the interfacial impedance increases, the current decreases rather than the voltage increases, and the system remains in a stable state rather than tending towards passivation. When local impedance abnormally accumulates, the current surge actively breaks down the passivation film. The electrochemical kinetic behaviors of these two control modes are fundamentally different.
[0030] The reason for introducing glycerol into the etching solution of this invention is that glycerol has three hydroxyl groups, is highly polar, and has a strong electron-donating ability. It can undergo physical adsorption (van der Waals forces, hydrogen bonds) and chemical adsorption with the metal / oxide film surface, and can also undergo electrostatic interaction and adsorption on charged surfaces. Furthermore, it can form a continuous hydrophobic organic layer on the metal surface, forming an organic protective film that physically blocks H2O, O2, and Cl. - H + When it comes into contact with the metal, it displaces the "hydration layer," forming a hydrophobic layer that blocks the anodic active sites and inhibits the anodic electrolysis rate (M→M). n+ +ne - ); Glycerol also reacts with Cl -The synergistic effect of metal ions and other substances forms a more uniform and dense protective layer, reducing the formation of pitting corrosion, inhibiting the electrolysis rate, and making the electrolysis process smoother. Therefore, it can inhibit interfacial reaction energy, change the surface state of the front edge of the alloy steel electrolysis surface, inhibit the occurrence rate of pitting corrosion, stabilize the electrolysis reaction, and avoid high rate in the early stage of electrolysis and excessively rapid decay of the electrolysis reaction in the later stage.
[0031] However, glycerol will increase the viscosity of the electrolyte, reduce the ion diffusion rate, encapsulate active sites, and reduce the efficiency of the electrolysis reaction. Care should be taken to control its upper limit. For corrosion of nitrides and carbonitrides, if it exceeds 8%, it will inhibit the electrolysis reaction and weaken the electrolysis effect.
[0032] Similar to glycerol, ethylene glycol, diethylene glycol, sorbitol, mannitol, xylitol, pentaerythritol, sodium gluconate, polyvinyl alcohol (PVA), and carboxymethyl cellulose (CMC) can all act as corrosion inhibitors to suppress reaction rates, reduce pitting corrosion, stabilize electrolytic reactions, and improve three-dimensional etching effects. When the amount of corrosion inhibitor added exceeds 8%, it will inhibit the electrolytic reaction and weaken the electrolytic effect. When the amount of corrosion inhibitor is less than 1%, its slow-release effect will be weakened and it will not be able to effectively achieve the slow-release effect. The recommended amount of corrosion inhibitor is 1~8%.
[0033] Compared with existing technologies, the core technological advantages of this application are as follows: (1) Compared with the existing constant current mode electrolysis method, the present invention adopts constant voltage mode to effectively overcome the passivation problem caused by microalloyed steel and alloy steel insulating phase (weakly conductive phase), and ensures the continuous and complete progress of the etching process. The present invention adopts constant voltage mode to lock the electrode potential, so that the current is adaptively adjusted according to the interface state: when the insulating phase accumulates at the interface and the interface impedance increases, the current drifts and jumps, breaking down the passivation film formed by the accumulation of the insulating phase, ensuring the continuous progress of electrolytic etching. In constant voltage mode, the electrode potential remains constant, the etching rate is stable and the surface flatness of the sample is more uniform.
[0034] (2) It is applicable to a wide range of steel grades, including microalloyed steel grades such as Mn-V series non-quenched and tempered steel, CrMo series quenched and tempered steel, and Cr-Mn-Ti series gear steel, as well as high alloy steel and stainless steel grades; it covers a comprehensive range of nitride / carbonitride precipitates, including TiN, VN / V(C,N), NbN / Nb(C,N), AlN, etc.
[0035] (3) The introduction of corrosion inhibitors can stabilize the interfacial reaction, suppress the rate of pitting corrosion, and make the electrolysis reaction stable, avoiding the problem of high reaction rate in the early stage of electrolysis, rapid decay in the later stage, and rapid failure of electrolyte. Attached Figure Description
[0036] Figure 1 The voltage-time-material weight loss curves under constant pressure etching mode for 40MnVS non-quenched and tempered steel; Figure 2 The voltage-temperature-material weight loss curves of 40MnVS non-quenched and tempered steel under constant pressure corrosion mode; Figure 3 Example 1: SEM images of AlN precipitates in 40MnVS non-quenched and tempered steel; Figure 4 Example 2: SEM images of TiN precipitates in 20CrMnTi gear steel; Figure 5 Example 3: SEM images of aggregated TiN precipitates in 53Cr21Mn9Ni4N (21-4N) austenitic valve steel; Figure 6 Example 4: SEM and EDS images of coupled Nb(C, N)-MnS precipitation in 46MnVNbS5 steel; Figure 7 SEM images of passivation phenomena in 3D corrosion of Comparative Example 1:40MnVS steel; Figure 8 Comparative Example 2: Electrolytic effect of three-dimensional corrosion on 20CrMnTi steel under constant voltage mode without corrosion inhibitor; Figure 9 SEM images of passivation phenomena during constant current corrosion of Comparative Example 3: 53Cr21Mn9Ni4N austenitic valve steel. Detailed Implementation
[0037] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0038] Nitrides / carbonitrides are important reinforcing precipitates in microalloyed and alloy steels, and their three-dimensional morphology (including shape, size, spatial distribution, and interfacial relationship with the matrix) has a decisive influence on the mechanical properties of the material. Several in-situ characterization methods for electrolytic etching have been disclosed in the prior art, all employing a constant current (constant current density) mode, using 20–300 mA / cm². 2 A constant current density is applied within a certain range to dissolve the metal matrix, gradually exposing the precipitated phase. This method is well-suited for ordinary carbon steel and low-alloy steel where oxides are the main non-metallic inclusions.
[0039] However, during the research process, the inventors discovered that for microalloyed steels containing microalloying elements such as Nb, V, Ti, and Al, and alloy steels containing alloying elements such as Cr, Ni, Mo, and W, the aforementioned constant current mode suffers from an insurmountable passivation failure problem, specifically manifested by the following three superimposed mechanisms: Firstly, insulating precipitates accumulate at the electrolysis interface, forming a high-resistivity layer. Nitrides / carbonitrides such as NbN, VN, TiN, AlN, Nb(C,N), and V(C,N) precipitated in microalloyed steels and alloy steels are insulators or weak conductors, with conductivity far lower than that of the metal matrix. As electrolysis progresses, undissolved precipitate particles continuously accumulate at the electrolysis interface, forming an insulating layer that forces the electrode potential to continuously increase under constant current conditions.
[0040] Secondly, the increased corrosion resistance of high-alloy matrices exacerbates the passivation trend. Alloy matrices containing elements such as Cr (especially Cr ≥ 5%), Ni, Mo, and W exhibit high corrosion resistance in non-aqueous organic electrolytes. They must maintain effective dissolution at higher electrode potentials. This, combined with the aforementioned accumulation effect of insulating phases, causes the electrode potential to rapidly enter and exceed the passivation potential range of the alloy matrix.
[0041] Third, once passivation is formed, etching is irreversibly interrupted. In constant current mode, in order to maintain the set current density, the power supply is forced to continuously increase the voltage until the device limit or the sample is damaged. The etching process is irreversibly interrupted, and effective three-dimensional morphology information cannot be obtained.
[0042] The technical problem to be solved by the present invention is to overcome the passivation and etching interruption caused by the accumulation of insulating nitrides / carbonitrides and other insulating phases during the electrolytic etching process of microalloyed steel and alloy steel, and to provide an electrolytic etching method suitable for microalloyed steel and alloy steel that can stably and completely realize the three-dimensional in-situ morphological characterization of nitrides / carbonitrides.
[0043] This invention, based on the three-dimensional etching device and etching solution formula for steel inclusions used in ZL 202010397749.X, improves the original electrolytic etching method and parameters by using a constant voltage power supply for electrolysis. Specifically, it uses a constant voltage power supply with adjustable voltage, allowing the voltage to be fixed during electrolysis while the current fluctuates with resistance. The voltage of the constant voltage power supply ranges from 6V to 64V. This constant voltage electrolytic etching mode eliminates the need for filtration, extraction, washing, and separation processes, enabling comprehensive and detailed observation of the three-dimensional morphology and spatial distribution of different types of nitrides / carbonitrides in microalloyed steel and alloy steel. It achieves in-situ exposure and analysis of nitrides / carbonitrides on a metal matrix, making the operation simple and efficient.
[0044] Another problem to be addressed is that the electrolyte exhibits excessively strong electrolytic capacity in the early stages, followed by a rapid decline in electrolytic effectiveness in the later stages. This invention solves this problem by optimizing the electrolyte formulation and introducing glycerol as a corrosion inhibitor. Specifically, this includes: improving the electrolyte formulation by increasing the amount of glycerol by 1-8% (by volume); and optimizing parameters such as the voltage, temperature range, and electrolysis time for three-dimensional etching to ensure sufficient exposure of nitrides / carbonitrides, showcasing their in-situ distribution characteristics within the matrix.
[0045] Adding glycerol to the electrolyte can inhibit the electrolysis reaction, change the surface state of the electrolytic front of the alloy steel, and form a continuous hydrophobic organic layer on the metal surface, creating an organic protective film that physically blocks H2O, O2, and Cl. - H + When in contact with the metal, the "hydration layer" is displaced, forming a hydrophobic layer that blocks the anodic active sites and the anodic electrolysis rate (M→M). n+ +ne - ); Glycerol also reacts with Cl - The synergistic effect of metal ions and other substances forms a more uniform and dense protective layer, reducing pitting corrosion, inhibiting the electrolysis rate, and making the electrolysis process smoother. Glycerol, as a corrosion inhibitor and electrolysis interface modifier, inhibits the self-corrosion, pitting corrosion, and side reactions of the base metal during electrolysis, thus acting as a corrosion inhibitor, improving the three-dimensional etching effect, and making the etching process more stable and durable.
[0046] When using a new formulation with corrosion inhibitors to perform three-dimensional etching electrolysis of microalloyed steel in constant voltage mode for nitride and carbonitride corrosion, the original etching temperature and etching time are no longer applicable. Therefore, this application screens the temperature and electrolysis time parameters for three-dimensional etching of different microalloyed steels.
[0047] This invention is applicable to microalloyed steel and alloy steel. The electrolytic etching device includes: a constant voltage power supply, an electrolytic cell (beaker), a cooling tank, cooling water, electrolyte, a thermometer, an anode clamp, a sample, a cathode, and connecting wires. The connection method of the device is as follows: the constant voltage power supply is used as the electrolytic power source; the beaker is placed in the cooling tank as the electrolytic cell, and the inside contains the electrolyte; the thermometer is used to monitor the real-time temperature of the electrolyte; the power supply, anode clamp, cathode, sample, and electrolyte are connected by wires to form a closed current loop.
[0048] The anode and cathode clamps of the etching apparatus are made of stainless steel to maintain good current stability. They are fixed with insulating rubber, with a distance of 20-30 mm between the cathode and anode. The bottom of the anode clamp and the cathode are kept at the same level to prevent the anode and cathode from touching the inner wall of the electrolytic etching tank. The cathode is a stainless steel sheet or platinum sheet with a size greater than 30×30 mm. The sample is connected to the anode, fixed with a non-conductive clamp, and immersed in the electrolyte. The observation surface (etched surface) of the sample faces the cathode. After etching, the sample is removed and repeatedly rinsed with anhydrous ethanol to remove residual electrolyte and reaction products. After drying, it is used for observation, analysis, and photographic statistics using scanning electron microscopy and energy dispersive spectroscopy. If the observation results are not ideal, the parameters can be adjusted to repeat the etching process.
[0049] The specimens for each embodiment and comparative example were all wire-cut into regular blocks of 10 mm × 8 mm × 6 mm (observation surface area is 10 mm × 8 mm, i.e., 0.80 cm²). 2 The non-observation surfaces were mechanically ground to remove the oxide layer and the deformation layer. The observation surfaces were successively polished with 400-grit, 800-grit, 1200-grit, 1500-grit, and 2000-grit sandpaper, and then mechanically polished to a mirror finish. They were then ultrasonically cleaned with anhydrous ethanol for 5 minutes and dried for later use. The etching device connection method, anode-cathode spacing (25mm), and post-processing procedures were the same as above. The following examples only describe their respective etching parameters and effects.
[0050] To further understand the present invention, the following embodiments are provided. It is worth noting that, unless otherwise specified, all raw materials used in the present invention are commercially available; and all methods and equipment employed are common in the art.
[0051] Example 1: 40MnVS microalloyed non-quenched and tempered steel was subjected to three-dimensional etching under constant pressure.
[0052] Chemical composition of the steel (mass fraction, %): C 0.40, Si 0.30, Mn 1.30, V 0.10, S 0.03, P 0.01, N 0.01, balance being Fe and unavoidable impurities; this steel has a high V content, which will precipitate nitrides such as VN and V(C,N) and carbonitrides during the solidification process; the alloy element content of this steel is low, and the corrosion resistance of the matrix is relatively weakest among the four steel grades in the examples.
[0053] Etching solution: Formula 1 (5% tetramethylammonium chloride + 15% acetylacetone + 5% glycerol + balance methanol); that is, 100 ml of etching solution contains 5g tetramethylammonium chloride, 15 ml acetylacetone, 5 ml glycerol, and 75 ml methanol.
[0054] Etching parameters: Constant voltage mode, etching was performed at -5℃ under different voltages, and the weight loss of the sample during the etching process at different times is shown in Table 1 below.
[0055] Table 1. Statistics of electrolytic weight loss of samples at different voltages at -5℃ (Δm / g) As can be seen from Table 1, when the voltage is less than 10V, the sample weight loss is small and the etching efficiency is low. When the voltage is greater than 30V, the sample weight loss rate is too fast, which can easily lead to the shedding of carbides and the instability and uncontrollability of the electrolysis process. When the voltage is in the range of 10V~30V, the sample weight loss range is moderate, indicating that the etching rate is appropriate at this time.
[0056] Table 2 shows the electrolytic weight loss data of 40MnVS steel samples after etching for 20 min at different temperatures and voltages under electrolytic formulation 1.
[0057] Table 2. Weight loss data (Δm / g) of 40MnVS steel samples at different temperatures and voltages. As can be seen from Table 2, when the temperature is below -5℃, the sample weight loss is small, and the etching rate and efficiency are slow and low; when the temperature is above 10℃, the sample weight loss is too fast, and the electrolysis process is prone to instability and is difficult to control; when the etching temperature is in the range of -5℃ to 5℃, the sample weight loss range is moderate, indicating that the etching rate is most suitable at this time.
[0058] Based on this, a voltage-time-material weight loss curve can be plotted for the electrolysis of the steel nitride / carbonitride, as shown below. Figure 1 As shown; similarly, based on the voltage-temperature-weight loss data, a graph showing the voltage-temperature-material weight loss variation pattern for the steel suitable for nitride / carbonitride corrosion can be plotted, as shown. Figure 2 As shown. Figure 1 , Figure 2 It can be used to guide the three-dimensional etching of nitrides / carbonitrides.
[0059] Example 1, from Figure 1 It can be seen that the overall electrolysis rate (weight loss rate) of the three-dimensional etching electrolysis ranges from approximately 0.001 to 0.2 g / min, with a relatively stable electrolysis rate of 0.02 to 0.08 g / min. At a voltage of 20V and an electrolysis time of 20 minutes, the weight loss rate is approximately 0.07 g / min, indicating a moderate electrolysis rate. Figure 2 It can be seen that at a voltage of 20V and a temperature of 0℃, the weight loss rate is about 0.07g / min, which is a moderate electrolysis rate.
[0060] For three-dimensional etching of microalloyed steel and alloy steel nitride / carbonitride, in constant voltage mode, the voltage control can be 10 V to 30 V, with a preferred control range of 10 V to 25 V; the electrolysis temperature control range is -5℃ to 5℃, preferably -5℃ to 0℃; in the constant voltage electrolysis mode for alloy steel, the recommended three-dimensional etching time is 10 min to 60 min, preferably 15 min to 25 min; during the etching process, the current is initially stable, and then exhibits periodic small-amplitude drift fluctuations as etching progresses, with no electrolysis interruption throughout the process, indicating a stable and controllable electrolysis process.
[0061] Figure 3 In Example 1, 40MnVS non-quenched and tempered steel was etched under Formula 1 at a voltage of 20V, a temperature of 0℃, and a time of 20 min. The resulting 3D SEM image of the nitrides shows that 20-30μm ultra-large hexagonal prism-shaped AlN precipitates are located in the corrosion pits of the matrix. The AlN morphology is regular, the three-dimensional outline is clear, and no insulating corrosion products or passivation film residues are observed on the surface. The color of AlN is significantly darker than that of the steel matrix, with obvious color contrast. This intuitively and powerfully confirms the successful implementation of the "constant voltage adaptive breakdown passivation film" mechanism of the present invention at the microscopic level: by adjusting the current, the polarization shielding effect caused by the insulating / weakly conductive phase of the nitride is effectively overcome, and the in-situ information of the inclusions in the steel matrix is preserved.
[0062] Example 2: 20CrMnTi gear steel is subjected to three-dimensional corrosion under constant pressure.
[0063] Chemical composition of the steel (mass fraction, %): C 0.22, Si 0.31, Mn 1.02, Cr 1.20, Ti 0.06, N 0.005, balance being Fe and unavoidable impurities. This steel contains Ti, with the main precipitated phase being TiN (hexagonal morphology); the Cr content of 1.20% moderately enhances the corrosion resistance of the matrix.
[0064] The etching solution uses optimized formula two: 3% triethanolamine + 8% m / V tetramethylammonium chloride + 3% glycerol + balance methanol; that is, 100 ml of etching solution contains 3 ml of triethanolamine, 8 g of tetramethylammonium chloride, 3 ml of glycerol, and 86 ml of methanol.
[0065] Etching parameters: constant voltage mode, set voltage 25V, etching time 15 min, etching solution temperature 0℃.
[0066] Corrosion results: (attached) Figure 4 This is a SEM image of TiN in 20CrMnTi steel. Figure 4As can be seen, two 4-5 μm dark black hexahedral TiN particles are embedded in the steel matrix. The three-dimensional morphology of the hexagon is clearly visible, and the three-dimensional effect is obvious. Energy dispersive spectroscopy confirms that they are TiN. The nitride surface is smooth and flat, and no passivation film residue is seen at the edge. At the same time, the photograph shows the appearance morphology of the gear steel matrix, proving the effectiveness of the "constant voltage adaptive breakdown passivation film" of the present invention, which completely preserves the original spatial coordinates and three-dimensional configuration information of the nitride in the steel matrix.
[0067] Observation of the etching process: During the etching process, the presence of Cr made the local corrosion resistance of the substrate higher than that in Example 1. The current showed several obvious jumps. After the jump, the current immediately dropped back to the normal level. Electrolysis continued without interruption.
[0068] Example 3: 53Cr21Mn9Ni4N (21-4N) austenitic valve steel is subjected to three-dimensional corrosion under constant pressure.
[0069] Chemical composition of the steel (mass fraction, %): C 0.53, Cr 21.0, Ni 4.0, Mn 9.0, Ti 0.15, N 0.40, Si 0.20, Al 0.03%, with the balance being Fe and unavoidable impurities; this steel contains a large amount of Cr (21%) and Ni (4.0%), and the matrix has extremely strong corrosion resistance, making it the steel with the greatest difficulty in electrolytic corrosion in the four sets of examples; the Ti and N contents are relatively high, and the main precipitated phase is TiN.
[0070] Etching solution: Formula 3 is used (7% m / V lithium chloride + 10% (volume ratio) γ-butyrolactone + 8% (volume ratio) glycerol + balance anhydrous ethanol; that is, 100 ml of etching solution contains 7g lithium chloride, 10 ml γ-butyrolactone, 8 ml glycerol, and 78 ml ethanol.
[0071] Etching parameters: constant voltage mode, set voltage 20 V, etching time 25 min, etching solution temperature 5℃.
[0072] Corrosion process observation: Due to the high corrosion resistance of the substrate, the current was small in the early stage of corrosion. As corrosion progressed, there were several large current jumps, and the jump amplitude was significantly greater than that in Example 1 and Example 2. In constant voltage mode, the system automatically adjusted the current to adapt to the changes in interface state, and there was no passivation interruption throughout the process.
[0073] Corrosion results: (attached) Figure 5The image shows a SEM image of TiN in 53Cr21Mn9Ni4N (21-4N) austenitic valve steel. Two hexahedral TiN particles are superimposed on a large austenitic matrix, suspended above the steel matrix. The austenitic matrix is smooth and exhibits a clear three-dimensional effect. The nitride surface is clean, with distinct outlines and no covering. The interface between the inclusions and the austenitic matrix is clear, and no passivation film residue is observed at the bottom or around the pit. This demonstrates the effectiveness of the "constant pressure adaptive breakdown passivation film" method of this invention. This invention successfully achieves non-destructive, clear, and in-situ exposure of the three-dimensional morphology of TiN, with a clear three-dimensional effect.
[0074] Example 4: 46MnVNbS5 microalloyed non-quenched and tempered steel is electrolyzed using a constant voltage mode.
[0075] Chemical composition of the steel (mass fraction, %): C 0.46, Si 0.65, Mn 1.16, V 0.16, S 0.06, P 0.02, Cr 0.27, Ni 0.15, Mo 0.05, N 0.02, Nb 0.035, with the balance being Fe and unavoidable impurities. This steel contains two microalloying elements, V and Nb, both of which are strong nitride / carbonitride forming elements; the precipitated phases include VN, V(C,N), and Nb(C,N); the steel contains alloying elements such as Cr, Ni, and Mo, which enhances the corrosion resistance of the matrix; Nb(C,N) is the most prominent factor in initiating the deposition of insulating phases at the electrolysis front in this system.
[0076] Etching solution: Formula 4 (5% m / V lithium chloride + 8% m / V citric acid + 4% (volume ratio) glycerol + balance anhydrous ethanol); that is, 100 ml of etching solution contains 5g lithium chloride, 8g citric acid, 4 ml glycerol, and 83 ml ethanol.
[0077] Etching parameters: constant voltage mode, set voltage 20V, etching time 25 min, etching solution temperature 5℃.
[0078] Observation of the etching process: During the etching process, the current exhibits a continuous surge characteristic of high frequency and small amplitude. The continuous dynamic adjustment of the current under constant voltage mode ensures that the electrolysis process is not interrupted.
[0079] Corrosion results: such as Figure 6 SEM and EDS surface scan images of Nb(C, N)-MnS coupled precipitation in 46MnVNbS5 steel. As can be seen from the images, light gray Nb(C, N) with a thickness of about 20 μm is superimposed and coupled with dark black MnS to form Nb(C, N)-MnS composite inclusions. These inclusions are embedded in the pitting corrosion pits of the non-quenched and tempered steel matrix, and the composite inclusions are partially covered by the non-quenched and tempered steel matrix. Figure 6The three-dimensional morphology of carbonitrides and their original information on solidification and precipitation in the steel matrix are intuitively displayed. The composition of the composite inclusion can be accurately identified by the surface scan distribution map of seven elements: Nb, V, Mn, S, C, N and Fe.
[0080] Comparative Example 1: 40MnVS steel is subjected to three-dimensional etching using constant current mode.
[0081] The steel composition is the same as in Example 1; the etching solution uses Formula 1 (same as in Example 1).
[0082] Etching parameters: constant current density 200 mA / cm² 2 The etching time was 25 min and the temperature was 0 ℃.
[0083] Observation of the etching process: After etching is started, the current is maintained at the set value, and the voltage continues to rise as etching progresses; thereafter, the voltage remains basically stable.
[0084] The results of the engraving are as follows: Figure 7 As shown, passivation occurs during the etching process under constant current etching mode, resulting in poor etching effect. Scanning electron microscopy shows that more than 60% of the observation surface is covered by insulating phase, with only a small amount of nitride precipitation visible in the edge area. The particle morphology is incomplete, and it is impossible to obtain the three-dimensional morphology and in-situ distribution information of the precipitated phase.
[0085] Comparative Example 2: 20CrMnTi steel is subjected to three-dimensional corrosion under constant pressure.
[0086] The steel composition is the same as in Example 2; the basic composition of the etching solution is Formula 2, but it does not contain glycerol corrosion inhibitor. That is: 3% triethanolamine + 8% m / V tetramethylammonium chloride + balance methanol; that is, 100 ml of etching solution contains 3 ml of triethanolamine, 8 g of tetramethylammonium chloride, and 89 ml of methanol.
[0087] Etching parameters: constant voltage mode, set voltage 25V, etching time 15 min, etching solution temperature 0℃.
[0088] Observation of the etching process: The current is large in the early stage of etching, fluctuating at about 0.5-0.8A. After 10 minutes, the current decreases significantly, to about 0.2~0.3A.
[0089] The results of the engraving are as follows: Figure 8As shown in the photo, the pitting corrosion reaction was severe during electrolysis, with a large area of the steel substrate peeling off and a large number of large-sized electrolytic pits forming on the surface. The electrolysis rate reached 0.2 g / min. The excessively high electrolysis rate (weight loss rate) caused severe side reactions such as self-corrosion and pitting corrosion in the metal substrate during the electrolysis process. The sample surface was uneven and had extremely poor flatness, making it impossible to obtain the three-dimensional morphology of the precipitated phase.
[0090] Comparing Example 2 and Comparative Example 2, it can be seen that under constant voltage electrolysis mode, the addition of glycerol as a corrosion inhibitor can effectively control the three-dimensional etching process, suppress severe pitting corrosion, and make the electrolysis process stable and continuous. The electrolysis rate of the metal surface can adapt to the environment, resulting in better flatness and more accurate three-dimensional effect.
[0091] Comparative Example 3: 53Cr21Mn9Ni4N (21-4N) austenitic valve steel is subjected to three-dimensional etching in constant current mode.
[0092] The steel composition is the same as in Example 3; the etching solution uses Formula 3, the same as in Example 3.
[0093] Etching parameters: constant current density 300 mA / cm² 2 The etching time and temperature were the same as in Example 3, with a time of 25 min and a temperature of 5°C.
[0094] The results of the engraving are as follows: Figure 9 As shown, passivation occurs during the etching process. The observation surface is almost entirely covered by a fine and dense insulating film, and the precipitated phase cannot be clearly displayed. Although the outline of the precipitated phase can be seen, the three-dimensional morphology is blurry and the effect is poor. This indicates that in high-Cr and high-Ni alloy steel, the three-dimensional etching effect of nitride / carbonitride in constant current mode is poor and it is difficult to overcome the electrolytic passivation phenomenon.
[0095] The foregoing has shown and described the basic process, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A three-dimensional etching method for nitrides and carbonitrides in steel, characterized in that, Includes the following steps: (1) Sample preparation: The micro-alloy steel or alloy steel sample is mechanically ground on each side to remove the oxide layer and the processing deformation layer. The observation surface is mechanically polished to mirror finish, then ultrasonically cleaned and dried. (2) Preparation of etching solution: Prepare a non-aqueous organic electrolytic etching solution with organic solvent as base liquid, containing electrolyte and metal ion complexing agent. The etching solution also contains 1-8% by volume glycerol as corrosion inhibitor. (3) Device connection: A constant voltage power supply is used as the electrolysis power supply. The anode clamp is connected to the sample. A stainless steel sheet or platinum sheet is used as the cathode. The anode clamp and the cathode are both fixed on the insulating support. The distance between the two electrodes is 20-30 mm. The bottom edge of the anode clamp and the cathode are at the same horizontal height. Neither electrode is in contact with the wall of the electrolytic cell. The observation surface of the sample faces the cathode and is immersed in the etching solution to form a closed electrolytic circuit. (4) Constant voltage electrolytic etching: Set the output voltage of the constant voltage power supply to 10V~30V, use constant voltage mode for electrolysis, electrolysis temperature -5℃~5℃, etching time 10 min~60 min; (5) Post-treatment and observation: After etching, the sample was taken out, rinsed repeatedly with anhydrous ethanol and dried. The three-dimensional morphology, composition analysis and in-situ distribution statistics of nitrides and carbonitrides on the etched surface were observed by scanning electron microscope and energy dispersive spectroscopy.
2. The method according to claim 1, characterized in that, The constant voltage power supply in step (4) is set to 10V~25V, the electrolysis temperature is -5℃~0℃, and the etching time is 15 min~25 min.
3. The method according to claim 1, characterized in that, The organic solvent in step (2) includes methanol or anhydrous ethanol; the electrolyte includes tetramethylammonium chloride or lithium chloride; and the metal ion complexing agent includes acetylacetone, triethanolamine, γ-butyrolactone or citric acid. The corrosion inhibitor may also be: ethylene glycol, diethylene glycol, sorbitol, mannitol, xylitol, pentaerythritol, sodium gluconate, polyvinyl alcohol (PVA), or carboxymethyl cellulose (CMC).
4. The method according to claim 1 or 3, characterized in that, The non-aqueous organic electrolytic etching solution formulation mentioned in step (2) includes one of the following four, wherein the volume fraction is based on the total volume of the etching solution, and the mass concentration is expressed in g / 100ml: Formula 1: 3-10% (m / V) tetramethylammonium chloride + 15-20% (V / V) acetylacetone + 1-8% (V / V) glycerol + balance methanol; Formula 2: 1-5% (V / V) triethanolamine + 4-10% (m / V) tetramethylammonium chloride + 1-8% (V / V) glycerol + balance methanol; Formula 3: 5-10% (m / V) lithium chloride + 10-15% (V / V) γ-butyrolactone + 1-8% (V / V) glycerol + balance anhydrous ethanol; Formula 4: 1-10% (m / V) lithium chloride + 1-10% (m / V) citric acid + 1-8% (V / V) glycerol + balance anhydrous ethanol.
5. The method according to claim 4, characterized in that, The etching solution is Formula 1, wherein the content of each component is: 5% (m / V) tetramethylammonium chloride + 15% (V / V) acetylacetone + 5% (V / V) glycerol + balance methanol.
6. The method according to claim 4, characterized in that, The etching solution is Formula 2, wherein the content of each component is: 3% (V / V) triethanolamine + 8% (m / V) tetramethylammonium chloride + 3% (V / V) glycerol + balance methanol.
7. The method according to claim 4, characterized in that, The etching solution is Formula 3, wherein the contents of each component are: 7% (m / V) lithium chloride + 10% (V / V) γ-butyrolactone + 8% (V / V) glycerol + balance anhydrous ethanol; Alternatively, the etching solution is Formula 4, wherein the content of each component is: 5% (m / V) lithium chloride + 8% (m / V) citric acid + 4% (V / V) glycerol + balance anhydrous ethanol.
8. The method according to claim 1, characterized in that: The three-dimensional etching electrolysis rate is 0.001~0.2 g / min, preferably 0.002~0.08 g / min.
9. The method according to claim 1, characterized in that, Step (4) Constant voltage electrolysis enables the current during the electrolysis process to be automatically adjusted according to the state of the electrolysis interface. Through the dynamic drift and sudden jump of the current, the accumulation and passivation of insulating phases at the electrolysis front caused by the enhanced corrosion resistance of microalloyed steel and alloy steel matrix and the weak conductivity of nitrides / carbonitrides are overcome, ensuring that the matrix continues to dissolve to expose nitrides and carbonitrides in situ.
10. The method according to claim 1, characterized in that, The steel types involved include: Mn-V series non-quenched and tempered steel, CrMo series quenched and tempered steel, Cr-Mn-Ti series gear steel and other microalloyed steel types, as well as high alloy steel, stainless steel and other steel types; the nitrides / carbonitrides involved in three-dimensional corrosion include: TiN, VN / V(C,N), NbN / Nb(C,N), AlN.
Citation Information
Patent Citations
A corrosive agent for preparing carbides in alloy steel and its preparation method, and a method for preparing carbides.
CN107541728B
Method for extracting carbide in hot work die steel
CN110618003A
Three-dimensional etching device and method for non-metallic inclusions in steel
CN111596094A
Musculoskeletal system control methods, systems, and devices based on velocity-precision tradeoffs
CN112757275B
A three-dimensional corrosion characterization method for non-metallic inclusions in high-nickel martensitic aged steel
CN112763523B